Porosity and biocompatibility study of ceramic implants based on ZrO[2] and Al[2]O[3] - Litvinova L. Larisa; Shupletsova V. Valeria; Leitsin V. Vladimir; Vasyliev R. Roman; Zubov D. Dmitry; Buyakov A. S. Ales Sergeevich; Kulkov S. N. Sergey Nikolaevich (2014, 2014)
Title screen